The role of trade credit in business operations - Białek-Jaworska, Anna; Nehrebecka, Natalia (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2016)
The paper aims to analyse the importance of trade credit in the financing of enterprises in Poland and to identify the determinants of the use of trade credit by Polish companies. Companies are granted trade credit by their suppliers while also extending them to their own recipients, therefore trade credit was analysed in net terms, i.e. the plus or minus sign and the difference between the trade credit obtained and extended in Poland. The trade credit received was measured as a trade liability without current expenses, i.e. adjusted by the current shortterm trade liabilities amounting to the average monthly expenditures on the core activity (1/12 of the material and energy consumption plus the cost of subcontracted services). The determinants of the net trade credit use include the company size, the industry it represents, the share of exports in sales and the proportion of foreign ownership in the share capital, as well as the interest rate channel and the currency rate channel in the monetary policy transmission. Analysis was based on Central Statistical Office panel data: annual reports F-02 for the years 1995−2011. A system GMM (robust) estimator was used to estimate the coefficients of the model. It has been shown that the low profitability of sales, a long-term payable (outstanding), a low debt capacity and a long cycle funds are good predictors of the use of trade credit. Higher growth opportunities and the greater ability to generate cash surpluses increase the trade credit extended. The increase in size of the company also increases the tendency to the trade credit extended and the volume of the trade credit extended, and decreases the propensity to received net trade credit and the volume of the received net trade credit. Monetary policy reduces companies’ inclination to extend trade credit and increases the volume of trade credit provision in the category of medium and large firms, but the interest rate channel increases the companies’ inclination to contract net trade credit and increases the volume of trade credit contracted.
Argumenta Oeconomica, 2016, Nr 2 (37), s. 189-231
Keywords: trade credit; liabilities; receivables; corporate finance; monetary policy; dynamic panel data models; system GMM